Check Point NGX R65 security administration - Bonnell, Ralph (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2008)
Check Point NGX R65 is the next major release of Check Point's flagship firewall software product, which has over 750,000 registered users. Check Point's NGX is the underlying security software platform for all of the company's enterprise firewall, VPN and management solutions. It enables enterprises of all sizes to reduce the cost and complexity of security management and ensure that their security systems can be easily extended to adapt to new and emerging threats. This title is a continuation of Syngress' best-selling references on Check Point's market leading Firewall and VPN products. * First book to market covering Check Point?s new, flagship NGX R65 Firewall/VPN. * Provides bonus coverage for Check Point?s upcoming NGX R65 Certification exams. * Companion Web site offers customized scripts for managing log files.
1: NGX R65 Operational changes -- 2: SmartClients and SmartManagement -- 3. Management Portal -- 4: Advanced Authentication -- 5: Advanced VPN Concepts and Tunnel Monitoring -- 6: Advanced VPN Client Installations -- 7: Multicast Security -- 8: Advanced DoS Protection -- 9: High Availability and Clustering -- 10: SecurePlatform.
Includes index.
Keywords: Firewalls (Computer security); Electronic books